Pengaruh Fear Of Missing Out, Word Of Mouth, Dan Social Enviroment Terhadap Keputusan Pembelian Iphone (Studi Kasus Pada Mahasiswa STMB Multismart) - Sofyan, Silvia; Hoki, Leony; Ali, Habib Akbar (Universitas Medan Area, 2025)
The iPhone has become a social status symbol, especially among college students. This study analyzes the influence of Fear of Missing Out (FOMO), Word of Mouth (WOM), and the Social Environment on iPhone purchasing decisions among 76 STMB Multismart students. The research method used a quantitative approach with a questionnaire and multiple regression analysis using SPSS 25. The results show that FOMO, WOM, and the Social Environment have a positive and significant influence on purchasing decisions. Simultaneously, they explain 69.5% of the variation in iPhone purchasing decisions. These findings have implications for marketers in designing strategies based on FOMO, WOM, and social influence, as well as the importance of consumer education on campus.